2011
DOI: 10.4085/1062-6050-46.2.160
|View full text |Cite
|
Sign up to set email alerts
|

Scapular-Muscle Performance: Two Training Programs in Adolescent Swimmers

Abstract: We describe the scapular-muscle characteristics of a group of adolescent swimmers. Both muscle-strength and muscle-endurance programs improved absolute muscle strength. Neither of the strength programs had a positive effect on scapular-muscle endurance. Our results may be valuable for coaches and physiotherapists when they are designing exercise programs for swimmers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 28 publications
(45 reference statements)
1
36
0
1
Order By: Relevance
“…Recently, specific exercises to strengthen the MT, LT, and SA were shown to be effective in restoring muscle balance. 31 Glenohumeral IR and ER ROM. In agreement with other studies, 3,18,19 we found side differences in the tennis players for IR, ER, and total ROM, with less IR, larger ER, and smaller total ROM on the dominant side.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, specific exercises to strengthen the MT, LT, and SA were shown to be effective in restoring muscle balance. 31 Glenohumeral IR and ER ROM. In agreement with other studies, 3,18,19 we found side differences in the tennis players for IR, ER, and total ROM, with less IR, larger ER, and smaller total ROM on the dominant side.…”
Section: Discussionmentioning
confidence: 99%
“…Vande Velde et al 116 showed that a 12-week scapular training programme resulted in a significant increase in isokinetic scapular muscle strength in healthy adolescent swimmers, and from a study of Merolla et al ,117 strength increase in the glenohumeral external rotators was apparent after a 6-month training programme in volleyball players with scapular dyskinesis. The latter study is of particular importance since it showed that scapular training improved glenohumeral muscle function, specifically the external rotators which are highly stressed during overhead activities.…”
Section: Scientific Rationale For a Scapular Rehabilitation Programmementioning
confidence: 96%
“…(Bak, 2010;Beach et al, 1992;Folland & Archer, 2014;Elizabeth E Hibberd & Myers, 2013; E.E. Hibberd et al, 2012;King, 1995;Lynch, Thigpen, Mihalik, Prentice, & Padua, 2010;Van de Velde, De Mey, Maenhout, Calders, & Cools, 2011) The high frequency and training of swimming can often lead to shoulder overuse injuries, or what Kennedy and Hawkin's originally described in 1978 as "swimmer's shoulder". (Blanch, 2004;Brushøj, Bak, Johannsen, & Faunø, 2007;Heinlein & Cosgarea, 2010;E.E.…”
Section: Introductionmentioning
confidence: 99%